CRIMINOLOGY DESCRIPTION OF JUVENILE CRIMINALS - Rustamov Javohir Sobir Ogli; Tokhtamurodov Muhriddin Bahriddin Ogli; Sayidjonov Sanjar Nodirjon Ogli (Western European Studies, 2023)
The article analyzes the criminological characteristics of the personality of juvenile offenders, their specific characteristics in personal character, the work carried out in our country on the prevention of crimes and offenses among minors, statistical data on crimes committed between minors, reviews of foreign lawyers on the criminological characteristics of the personality of juvenile offenders
Keywords: Investigator; preliminary investigation; prosecutor's supervision